Regulation of Cell Death Mechanisms by Melatonin: Implications in Cancer Therapy - Wang, Zicheng; Liu, Yanqing; Musa, Ahmed E. (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Cancer therapy is based on the killing of cancer cells using various therapeutic agents, such as radiation, chemotherapy or targeted therapy drugs, and immunotherapy. Cancer cells may undergo apoptosis, mitotic catastrophe, necrosis, autophagy, mitophagy, senescence, etc., depending on the therapeutic modality and nature of cancer cells. Mutations in some critical genes, such as p53 and Phosphatase and Tensin Homolog (PTEN) tumor suppressor genes, are associated with immune escape of cancer cells and tumor progression. Furthermore, the overexpression of some genes. such as phosphatidylinositol-3-kinase (PI3K), Nuclear Factor of Kappa B (NF-ΚB), cyclooxygenase-2 (COX-2) and mammalian Target of Rapamycin (mTOR), is associated with the resistance of cancer cells to various types of cell death. Melatonin is known as a circadian regulator hormone that has several anti-cancer properties. It has the ability to activate tumor suppressor genes and attenuate the expression of survival genes in cancer cells. Modulation of cell death or survival genes that have been disrupted or overexpressed in cancer cells can improve cancer therapy. In this review, we explain the potential of melatonin in regulating various mechanisms of cancer cell death.
Keywords: cancer